2012
DOI: 10.1016/j.energy.2012.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Combining optimisation and simulation in an energy systems analysis of a Swedish iron foundry

Abstract: To face global competition, and also reduce environmental and climate impact, industrywide changes are needed, especially regarding energy use, which is closely related to global warming. Energy efficiency is therefore an essential task for the future as it has a significant impact on both business profits and the environment. For the analysis of possible changes in industrial production processes, and to choose what changes should be made, various modelling tools can be used as a decision support. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…[2, 16,[41][42][43]45,48,53,61,76,87] Energy modelling and simulation Use computer programs and software tools for modelling and simulation of process operations and energy flows to identify energy saving opportunities. [1,6,11,16,22,30,32,[40][41][42]46,48,53,61,63,75,80,81,85] Energy manager and/or team Employ a (full-time) energy manager, close to the CEO, responsible for energy consumption, internal communication, and effectiveness of the energy management program and equipped with the necessary authority for energy efficiency investments.…”
Section: Continual Improvementmentioning
confidence: 99%
See 2 more Smart Citations
“…[2, 16,[41][42][43]45,48,53,61,76,87] Energy modelling and simulation Use computer programs and software tools for modelling and simulation of process operations and energy flows to identify energy saving opportunities. [1,6,11,16,22,30,32,[40][41][42]46,48,53,61,63,75,80,81,85] Energy manager and/or team Employ a (full-time) energy manager, close to the CEO, responsible for energy consumption, internal communication, and effectiveness of the energy management program and equipped with the necessary authority for energy efficiency investments.…”
Section: Continual Improvementmentioning
confidence: 99%
“…Energy efficiency is an essential task for the future [1]. According to the international standard ISO 50001 [2], energy is "electricity, fuels, steam, heat, compressed air, and other similar media", while energy efficiency is the "ratio or other quantitative relationship between an output of performance, service, goods, commodities, or energy, and an input of energy".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mardan et al stated the combination steps of discrete-event simulation and energy system optimization. A case study was used to show how these two tools benefit each other and achieve the optimal and feasible results [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Simulation modelling tools may be complemented by other modelling tools that enhance the support for decisions. Mardan and Klahr [2] have shown that an optimisation tool may be a very powerful complement to a simulation tool. By combining these tools this may increase the reliability of the results, but it also enhances the possibility of finding better solutions.…”
Section: Introductionmentioning
confidence: 99%